1989
DOI: 10.1007/bf02309916
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional and M-mode assessment of aortic growth in the normal and growth-retarded (IUGR) human fetuses

Abstract: This study compares human fetal aortic dimensions in 128 normal and 30 intrauterine growth-retarded (IUGR) fetuses using two-dimensional (2D) and M-mode echocardiography. We found that the fetal aortic root in the normally grown fetuses is significantly larger than the descending aorta at all gestational ages. Furthermore, IUGR fetuses had smaller descending aortic dimensions then did normally grown fetuses. When the descending aortic dimension in the IUGR fetuses was corrected for estimated fetal weight, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…The volume and pattern of flow through a developing structure influence its growth 23 . The reduction of somatic growth seen in growth restriction is accompanied by a reduction in the aortic and the peripheral vascular bed size, but not in the heart 24 . Analysis W confirmed that aortic dimensions in GR fetuses were equivalent to those in younger, normally grown fetuses of similar mean fetal weight, but were smaller, as were the semilunar valves, when fetuses were gestationally matched.…”
Section: Discussionmentioning
confidence: 95%
“…The volume and pattern of flow through a developing structure influence its growth 23 . The reduction of somatic growth seen in growth restriction is accompanied by a reduction in the aortic and the peripheral vascular bed size, but not in the heart 24 . Analysis W confirmed that aortic dimensions in GR fetuses were equivalent to those in younger, normally grown fetuses of similar mean fetal weight, but were smaller, as were the semilunar valves, when fetuses were gestationally matched.…”
Section: Discussionmentioning
confidence: 95%
“…31,32 It was further observed that reduction of somatic growth in IUGR was accompanied by a reduction in the peripheral vascular bed size. 31 However, after correction for estimated fetal weight, the fetal aortic vessel diameters were found to be comparable to those of the normally grown fetuses, thus indicating that the discrepancy between body habitus and vessel size observed in our study may possibly be a phenomenon occurring after birth.…”
Section: Discussionmentioning
confidence: 99%
“…An anderer Stelle haben wir bereits darauf hingewiesen, dass dabei neben dem regelrechten Abgang und Verlauf von Aorta und Truncus pulmonalis vor allem auf die Kaliber dieser Gefasse geachtet werden sollte [1], Über Messungen der Durchmesser der Aorten-und Pulmonalklappe beim Feten ist in den letzten 10 Jahren von mehreren Arbeitsgruppen berichtet worden [5,6,[8][9][10][11][12][13][14][15][16][17][18]. In den früheren Arbeiten wurden die Gefässdurch-messer vorwiegend im M-Mode-Verfahren gemessen [5,9,17,18], Ähnlich wie bei den Messungen des Septums und der Myokarddicke der Ventrikel muss bei solchen Messungen die M-Markierung senkrecht zu der entspre chenden Struktur eingestellt werden [6], Dies ist zum ei nen nicht bei jeder Lage des Feten möglich, zum anderen ist der M-Mode für «Nichtkardiologen», die zunehmend die Beurteilung des Herzens eines Feten anstreben, oft nicht verständlich bzw. schwer praktikabel [4,6], Die Herzbiometrie im M-Mode wurde bislang immer mit der Begründung verteidigt, dass sie eine genaue Abgrenzung der Gefässwand mit einer präzisen zeitlichen Orientie rung ermöglicht [13], Mit den modernen Geräten sind aber Messungen im B-Bild (Real-time)-Modus durch die hohe Auflösung und die Zoom-Technik sehr präzis gewor den.…”
Section: Diskussionunclassified
“…SSW auf 10 mm am Termin. Diese Ergebnisse decken sich bis auf wenige Abweichungen mit denen anderer Autoren [5,6,8,9,11,14,17,18]. In Tabelle 1 wird am Beispiel des Aortenklappendurchmessers in der 24.…”
Section: Diskussionunclassified
See 1 more Smart Citation